Astragaloside IV alleviates myocardial ischemia-reperfusion injury in rats through regulating PI3K/AKT/GSK-3β signaling pathways - Wei,Dajun (2019)
Abstract Purpose: To investigate the effect of astragaloside IV (As-IV) on myocardial ischemia-reperfusion (I/R) injury in rats and reltaed mechanisms. Methods: Sixty rats were randomly divided into sham-operated, control I/R and 2.5, 5 and 10 mg/kg As-IV groups, 12 rats in each group. The later three groups were intragastrically administered with As-IV for 7 days, with a dose of 2.5, 5 and 10 mg/kg, respectively. The myocardial I/R injury model was constructed in later four groups. At the end of reperfusion, the cardiac function indexes, serum lactate dehydrogenase (LDH) and creatine kinase (CK) levels, heart weight (HW)/body weight (BW) ratio and infarct size, and expressions of phosphatidylinositol-3 kinase/serine-threonine protein kinase (PI3K/AKT) and glycogen synthase kinase-3β (GSK-3β) proteins and the phosphorylated forms (p-AKT, p-GSK-3β) were determined. Results: Compared with control I/R group, in 5 and 10 mg/kg As-IV groups the left ventricular systolic pressure, fractional shortening and ejection fraction were increased, the left ventricular end-diastolic pressure was decreased, the serum LDH and CK levels were decreased, the HW/BW ratio and myocardial infarct size were decreased, and the p-Akt/Akt ratio and p-GSK-3β/GSK-3β ratio were increased (all P < 0.05). Conclusion: As-IV can alleviate the myocardial I/R injury in rats through regulating PI3K/AKT/GSK-3β signaling pathways.